2019
DOI: 10.1042/bsr20180672
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity and pharmacokinetic characterization of Cereus jamacaru ethanolic extract in rats

Abstract: The effect of Cereus jamacaru ethanolic extract in rats was analyzed using genotoxicity assays and liver ABCB1 and CYP2D4 gene expression. The lyophilized extract of C. jamacaru cladodes was analyzed with LC–MS/MS. Male Wistar rats (n=36) were equally distributed into six groups that did (+) or did not (−) receive cyclophosphamide treatments: Control (−); Control (+); EXP 1 (−), and EXP 1 (+), both treated with 210 mg/kg of ethanolic extract; and EXP 2 (−) and EXP 2 (+), both treated with 420 mg/kg of ethanoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
0
4
1
1
Order By: Relevance
“…A previous study performed by Davet (2005) has identified alkaloids and steroids as the main compounds contained in C. jamacaru cladodes, corroborating with the finding ones of this study and scientific literature for Cactaceae. More recently, Medeiros et al (2018) have identified almost 24 phytochemicals in C. jamacaru, including tannins that have not been identified in our study.…”
Section: Qualitative Identification Of the Main Compound Classescontrasting
confidence: 50%
See 2 more Smart Citations
“…A previous study performed by Davet (2005) has identified alkaloids and steroids as the main compounds contained in C. jamacaru cladodes, corroborating with the finding ones of this study and scientific literature for Cactaceae. More recently, Medeiros et al (2018) have identified almost 24 phytochemicals in C. jamacaru, including tannins that have not been identified in our study.…”
Section: Qualitative Identification Of the Main Compound Classescontrasting
confidence: 50%
“…We found several secondary metabolites in C. jamacaru, including alkaloids, terpenoids, phenols, and saponins. These compounds were also identified in the studies performed by Cartaxo et al (2010), Schwarz et al (2010), Bevilaqua et al (2015), Santos et al (2019), Dutra et al (2019) and Medeiros et al (2018).…”
Section: Qualitative Identification Of the Main Compound Classesmentioning
confidence: 70%
See 1 more Smart Citation
“…e in vivo micronucleus test, first developed in mouse bone marrow erythrocytes, is one of the genotoxicity tests recommended by international regulatory agencies and government institutions for the evaluation of new substances [24]. Micronuclei (MN) are extranuclear bodies that contain damaged chromosome fragments and/or whole chromosomes that were not incorporated into the nucleus after cell division.…”
Section: Discussionmentioning
confidence: 99%
“…A espécie é de ampla distribuição nas regiões áridas e semiáridas, servindo como recurso forrageiro para alimentação de animais [3]. Além disso é utilizada na medicina tradicional para o tratamento de úlceras e doenças do trato respiratório devido ao elevado conteúdo de compostos bioativos com potencial de uso fitoterápico [4].…”
Section: Introductionunclassified